Program Kuliah Kerja Nyata dan Pembentukan Civic Disposition Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau - Tasya Chika Setiaulia; Hambali Hambali; Kingkel Panah Grosman (Universitas Muhammadiyah Ponorogo, 2026)
Program Kuliah Kerja Nyata (KUKERTA) is a form of learning that integrates knowledge in the form of real work practice aimed at developing students' academic, social, and citizenship competencies. However, in practice, there are still students from the Faculty of Teacher Training and Education (FKIP) at the University of Riau who feel that their civic disposition has not developed optimally after participating in KUKERTA. Therefore, this study aims to analyze the effect of the KUKERTA program on the civic disposition of FKIP students at the University of Riau. This study uses a quantitative approach with an associative-causal survey method. The population and sample of this study consisted of 41 FKIP students who participated in the regular KUKERTA program in 2025. Data were collected through questionnaires and documentation and then analyzed using simple linear regression, which showed that the KUKERTA program had a positive and significant effect on students' civic disposition. The coefficient of determination (R square) value of 40.7% indicates that KUKERTA contributes significantly to students' civic disposition. Thus, the KUKERTA program has proven to be effective as a learning tool to strengthen students' civic disposition and support the development of educators with good character.